Perceptions of Prospective Mathematics Teachers on Online Learning during Covid-19 Pandemic: Difficulties, Strategy, and Satisfaction - Rohati; Harina Fitriyani; Yaya S. Kusumah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The emergence of the Covid-19 pandemic has created a great degree of uncertainty about the future of education and has required teachers and students to shift from face-to-face to online learning. This study analyze prospective mathematics teachers' perceptions of online learning. This research was conducted using a survey method to see the perceptions of prospective mathematics teachers in online learning mode. Respondents comprised 953 prospective mathematics teachers from 34 provinces in Indonesia, consisting of 172 men and 781 women. Instruments used to collect data were questionnaires and open questions. Based on the percentage results of each of the findings of this study, the data is presented and analyzed more qualitatively. There are three main findings in this study. First, prospective mathematics teachers experience problems in online learning, namely problems with technology, networking, internet quota, motivation and self-management, lecturer constraints, number of courses, socioeconomic factors, learning resources, interactions with peers, and health problems. Second, prospective teachers have strategies to overcome this, including increasing peer collaboration, managing study time, and optimizing learning resources. Third, prospective teachers express dissatisfaction with the implementation of online learning and the reasons for this dissatisfaction. This research has implications for teachers and prospective mathematics teachers to understand online learning by utilizing ICT and increasing efforts to be independent.